Morellia (Morellia) aenescens Robineau-Desvoidy 1830 ... - Pamplona, Denise; Nihei, Silvio S.; Couri, Márcia S.; Pont, Adrian C. (Zenodo, 2016)
2. Morellia (M.) aenescens Robineau-Desvoidy, 1830 (Figs 7–12) Morellia aenescens Robineau-Desvoidy, 1830: 406. Type locality: FRANCE, Saint-Sauveur. Syntypes, formerly in Robineau- Desvoidy collection, now destroyed (not MNHN; see Evenhuis et al. 2010). Muscina concolor Robineau-Desvoidy, 1830: 408. [Junior secondary homonym, preoccupied in Morellia by Morellia concolor Robineau-Desvoidy, 1830.] Type locality: FRANCE, Saint-Sauveur. Syntypes: ♀♀, formerly in Robineau-Desvoidy collection, now destroyed (not MNHN; see Evenhuis et al. 2010). Curtonevra curvipes Macquart, 1834a: 12; 1834b: 148. Type locality: FRANCE, Lille district. Type location: Lectotype ♂, MHNL (des. Pont 2012: 57; seen). Cyrtoneura valga Wahlberg in Zetterstedt, 1845: 1348. Type locality: SWEDEN, Lule Lappmark, Kvikkjokk. Syntypes: ƋƋ, probably in NHRS but not recognised (Pont 2011: 63). Camilla fuscana Robineau-Desvoidy, 1863: 642. Type locality: FRANCE, Paris district. Holotype/syntypes Ƌ, formerly in Robineau-Desvoidy collection, now ... : Published as part of Pamplona, Denise, Nihei, Silvio S., Couri, Márcia S. & Pont, Adrian C., 2016, Taxonomy of Morellia Robineau-Desvoidy (Diptera: Muscidae): revision of the subgenera Morellia s. str. and Parapyrellia Townsend, pp. 1-110 in Zootaxa 4163 (1) on pages 15-16, DOI: 10.11646/zootaxa.4163.1.1, http://zenodo.org/record/259278 ...